2016
DOI: 10.1017/s0007114516003202
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between 25-hydroxyvitamin D concentration in early pregnancy and pregnancy outcomes in a large, prospective cohort

Abstract: Type of publicationArticle (peer-reviewed)Link to publisher's version http://dx.doi.org/10.1017/S0007114516003202Access to the full text of the published version may require a subscription. Rights © The Authors 2016Embargo information Access to this article is restricted until 12 months after publication by the request of the publisher Abstract Vitamin D insufficiency and deficiency have been associated with an increased risk of adverse pregnancy outcomes. Controversy remains as findings have been inconsistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 42 publications
3
43
0
2
Order By: Relevance
“…However, recent large‐scale studies not included in these meta‐analyses reported no relationship between 25(OH)D and post‐OGTT glucose levels or GDM risk . Most of these studies involved predominantly non vitamin D deficient women (25(OH)D > 70–132 nmol/L). This may explain their null findings since relationships between vitamin D and glucose metabolism are thought to be more pronounced in vitamin D deficient women .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent large‐scale studies not included in these meta‐analyses reported no relationship between 25(OH)D and post‐OGTT glucose levels or GDM risk . Most of these studies involved predominantly non vitamin D deficient women (25(OH)D > 70–132 nmol/L). This may explain their null findings since relationships between vitamin D and glucose metabolism are thought to be more pronounced in vitamin D deficient women .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1639 were excluded after reading titles and/or abstracts, and 75 articles were subjected to a full-text review. After reading the full text, a total of 24 cohorts were invited to participate, which included 13 cohort studies [27][28][29][30][31][32][33][34][35][36][37][38][39], seven case-control studies [40][41][42][43][44][45][46] and four cross-sectional studies [47][48][49][50].…”
Section: Search Resultsmentioning
confidence: 99%
“…Because three studies [29][30][31] of 24 measured serum 25(OH)D concentrations at two or three periods of pregnancies, our meta-analysis included nine studies [28][29][30][31]36,39,41,44,46] in the first trimester, 11 studies [27,[30][31][32][33][34][35]37,38,40,43] in the second trimester, and nine studies [29][30][31]42,45,[47][48][49][50] in the third trimester.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations